Pulse Waves How Vascular Hemodynamics Affects Blood Pressure - Salvi, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This new, revised and updated edition takes into account the most recent advances in the understanding of human pathophysiology. The book presents the complex basic principles of vascular hemodynamics and its pathophysiology in a direct and effective way, stressing the importance of the mechanical properties of large arteries in the origin of blood pressure. The readily understandable text, supported by helpful images, describes the elements that define blood pressure and explains such important concepts as pulse wave velocity, central blood pressure, reflected waves, and pulse pressure amplification. Entirely new chapters are included on the sympathetic nervous system and arterial stiffness and on the role played by arterial stiffness in influencing blood pressure variability. The book will enable the physician to answer some of the key questions encountered when addressing the problem of arterial hypertension in everyday clinical practice: How is blood pressure generated? How should blood pressure values be interpreted? Is systolic blood pressure of greater importance than diastolic blood pressure?
1 Blood Pressure and Vascular Hemodynamics -- 2 Pulse Wave Velocity and Arterial Stiffness Assessment -- 3 Arterial Stiffness and Blood Pressure Variability -- 4 Central Blood Pressure: Part 1, pathophysiology -- 5 Central Blood Pressure: Part 2, Pulse Wave Analysis -- 6 Aortic Stiffness and Myocardial Ischemia -- 7 Arterial Stiffness in Chronic Kidney Disease -- 8 Pulse Wave Velocity and Pulse Wave Analysis in Experimental Animals.
Keywords: Medicine; Human physiology; Angiology; Cardiology; Phlebology; Medicine & Public Health; Cardiology; Angiology; Phlebology; Human physiology